An Investigation of the Equivalent Meaning of Translation of Idiomatic Expressions in a Movie - Ika Apriani Fata; Burhansyah Burhansyah; Monalisa Ariska; Sofyan A Gani (Proceedings of AICS - Social Sciences, 2021)
This study aimed to look at the translator's translation tactics and determine which ones are utilized the most and which ones are used the least. In the movie Grown Ups, the researcher focused on the translation procedures in idiomatic idioms from English to Indonesian. The method of data collecting in this study was content analysis, and the research design was descriptive qualitative. The researcher used Baker's (2018) theory to categorize the different types of translation strategies, which include: 1) using an idiom with similar meaning and form, 2) using an idiom with similar meaning but dissimilar form, 3) borrowing the source language idiom, 4) translation by paraphrase, 5) translation by omission of a play on idiom., and 6) translation by omission of the entire idiom. The results revealed that the movie contained 94 idiomatic expressions, with the most common strategy being translation by paraphrasing (62 data or about 65.96 percent), followed by translation by omission of a play on idiom (21 data or 22.34 percent), translation by omission of a play on idiom (four data or 4.25 percent), and using an idiom of similar meaning and form (three data or about 3.19 percent). Furthermore, the translator's least-used tactics were adopting the source language's idiom and translation by excluding the full idiom with two data points each, accounting for 2.13 percent of the total. These tactics assist the translator in overcoming the challenge of translating idiomatic terms, as well as make the translation results enjoyable and acceptable to the audience.Keywords: Translation, idiom, American movie, translation strategies.